(untitled) (Research, Society and Development, 2020)
The objective of this work was to evaluate the health of a soil under an integrated crop-livestock-forest system through multivariate analysis of the physical, chemical and physical-hydric attributes of the soil. The experiment was carried out in a Albaquults with a sandy texture in the municipality of Alagoinha, PB, under the following consortia in a randomized block design: i) Br. Decumbens + Gliricidia sepium (BG); ii) Br. decumbens + Mimosa caesalpiniifolia (BS); iii) Br. decumbens + Tabebuia alba (BI); iv) Br. decumbens + Zea mays (LA); v) Brachiaria decumbens (BD). Samples (deformed and undeformed) of soil were collected to evaluate physical, physical-hydric and chemical properties of the soil in the layers of 0.0-0.1, 0.1-0.2 and 0.2-0.3 m. The averages were analysed using principal component analysis and Pearson’s correlation (P<0.05). The results indicated that LA managed to group the largest number of properties related to the structural quality of the soil. The soil density showed positive and negative correlations with most of the analysed physical variables. Regarding the chemical properties, a greater clustering was detected in the LA and BG systems in the 0-0.1 cm layer. We conclude that multivariate analysis is a viable option for assessing soil health, since its groups as many properties as possible within the most prevalent management system.